WAYS OF TEACHING VOCABULARY AND MILITARY TERMS TO CADETS IN ENGLISH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
A lexical approach to teaching means the primary focus is on helping cadets acquire vocabulary. In English language teaching methods are systems for structuring lessons while approaches are less concerned with how the lesson is structured and more concerned with the general focus of instruction. This article deals with the notion of lexical skills, structure, qualities, stable conditions for the formation of lexical skills, as well as steps that passes every new lexical unit. All this must be taken into account in the process of learning a foreign language vocabulary.